Casting characteristics of magnesium-lithium alloys - Singh R.K.; Sudhakar B.; Chakravorty C.R.; Tiwari S.N. (My University, 2025)
An attempt has been made to develop a suitable foundry process for production of highly reactive magnesium-lithium alloy castings. This process would permit the manufacture of shaped castings to complement the already developed wrought materials for aerospace applications. This paper presents results for two important casting characteristics of the alloy: fluidity and metal-mould reactions. Dependence of the alloy fluidity on superheat and lithium content has been evaluated and the results indicate a major influence of oxidation, particularly at higher superheat. The extent of surface degradation and depletion of lithium from the surface of the casting poured in various sand moulds have also been studied. Various reactions occurring between molten metal and mould materials have been predicted based on thermodynamic considerations and verified by analysing the reaction products. The results indicate that zircon sand with no-bake organic binder is the ideal mould material for producing shaped castings of magnesium-lithium alloys. The use of graphite coat in the mould cavity was found to further reduce the interaction between the molten metal and the mould material.